(untitled) (International Journal of Physiotherapy, 2016)
Background: In this advanced era, neck and back pain has become a common musculoskeletal problem. These symptoms have a high prevalence in the community and now they are affecting even our adolescents leaving a major impact on youth’s functional and educational activities. Nevertheless, the burden of these musculoskeletal pains, which relates not only to its prevalence but also to increase in physiological and psychological stress among them, distressing their creativity. Madrassa students have a daily exposure to neck and back pain due to poor posture. The McKenzie method is a popular treatment for back and neck pain among physical therapists. So, the intention of this study is to test the effectiveness of McKenzie exercises in neck and back pain, because hardly any data is available on McKenzie technique and its outcome in Pakistan. The objective of the study is to determine the effectiveness of McKenzie exercises in reducing neck and back pain among madrassa students. Methods: The students were recruited from Madrassa Darul Akram (Baldia town) and Jamia Ashraf-ul-madrassa (Gulshan-e-Iqbal) Karachi. One sixty three students aged between 12–18 years of both genders who were fulfilling the inclusion criteria were selected from Madrassa Darul Akram (Baldia town) and Jamia Ashraf-ul-madrassa (Gulshane-Iqbal). The participants received McKenzie exercises programs intervention for three consecutive weeks. Outcome Measure: Neck Disability Index (NDI), Modified Oswestry Low Back Pain Disability Index (ODI) and Numeric Pain Rating Scale (NPRS) Results: The present study showed significant results in all three scales in both genders (p<0.001).Among sections, the Hafiz students revealed greater score in all 3 scales before treatment as compared to ‘Alim/Alima’ and ‘Nazra’ students and after treatment showed significant results in all 3 domains (p<0.001). Conclusion: Findings of this study revealed that madrassa students were more prone to develop neck and back pain. This might be either because of strict enforcement by teachers or usual poor sitting habit. Most of the time, it is difficult for students to come regularly for therapy sessions. It is concluded that McKenzie exercises had significantly reduced the neck and back pain among madrassa students.